Kreativitas siswa melalui Kegiatan Kolase dengan Pemanfaatan Daur Ulang Sampah di Kelas IV SD Negeri Garot Aceh Besar - Tara Zulia Putri; Fauzi Fauzi; Aida Fitri (Universitas Syiah Kuala, 2023)
Collage is a technique in painting by gluing or gluing pieces of waste materials or used goods on the drawing area so as to produce a new work of art. The formulation of the problem in this study is how the level of Student Creativity through Collage Activities on the Utilization of Waste Recycling in Class IV SD Negeri Garot Aceh Besar. This study aims to describe the level of Student Creativity through Collage Activities on the Utilization of Waste Recycling in Class IV SD Negeri Garot Aceh Besar. This study uses a qualitative approach with a descriptive type of research. This research was conducted in the fourth grade of SD Negeri Garot Aceh Besar with the research subjects being grade IV/B teachers and 20 students consisting of 8 boys and 12 girls. Data collection techniques in this study were observation, and interviews. Based on the results of the study, based on 4 criteria assessed, namely fluency, flexibility, originality, and detail, 9 students or 45% had creativity and 11 students or 55% had low creativity. So, it can be concluded that students' creativity in making works from collage activities using waste recycling is in the sufficient category, namely 45%.